Catching the Perpetrators of Dangerous Cosmetics: Between Intention and Absolute Responsibility - Darmawanto Darmawanto; Muhammad Rinaldy Bima; Muhammad Fauzi Ramadhan (HORIZON PUBLIC LEGAL STUDIES, 2026)
The circulation of illegal cosmetics containing hazardous substances represents a serious issue that not only threatens public health but also reflects the inadequacy of criminal liability enforcement against business actors. This study aims to analyze the regulatory framework governing criminal liability for illegal cosmetic business actors and to examine the elements of criminal responsibility in judicial practice. This research employs a normative juridical method with statutory, conceptual, and case approaches. The novelty of this study lies in integrating classical criminal liability concepts with strict liability principles within the modern consumer protection framework. The findings reveal that although the criminal regulatory framework is comprehensive and layered, its implementation still faces challenges, particularly in proving fault elements and ensuring effective law enforcement. Judicial practices also demonstrate a tendency to apply the lex specialis principle and implicitly recognize strict liability to enhance consumer protection. This study concludes that strengthening a consumer-oriented criminal liability paradigm and improving institutional coordination are essential to suppress the proliferation of hazardous illegal cosmetics.